2008
DOI: 10.1124/mol.108.048843
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Nicotine Treatment Differentially Regulates Striatal α6α4β2*and α6(Nonα4)β2*nAChR Expression and Function

Abstract: Nicotine treatment has long been associated with alterations in ␣4␤2* nicotinic acetylcholine receptor (nAChR) expression that modify dopaminergic function. However, the influence of longterm nicotine treatment on the ␣6␤2* nAChR, a subtype specifically localized on dopaminergic neurons, is less clear. Here we used voltammetry, as well as receptor binding studies, to identify the effects of nicotine on striatal ␣6␤2* nAChR function and expression. Long-term nicotine treatment via drinking water enhanced nonbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
104
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(123 citation statements)
references
References 43 publications
16
104
3
Order By: Relevance
“…Purely ␣6 or mixed ␣4␣6 receptors may have different pharmacological and physiological, and perhaps also cell biology, properties. The mixed ␣4␣6␤2 receptor has higher affinity for nicotinic agonists than the ␣6␤2 receptor , and chronic nicotine (Perez et al, 2008) has opposite effects on the expression of these subtypes in the striatum. These findings may possibly explain the recent evidence of a dominance of purely ␣6*-sensitive responses in the nAc, whereas ␣4 responses dominate in the CPu (Exley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Purely ␣6 or mixed ␣4␣6 receptors may have different pharmacological and physiological, and perhaps also cell biology, properties. The mixed ␣4␣6␤2 receptor has higher affinity for nicotinic agonists than the ␣6␤2 receptor , and chronic nicotine (Perez et al, 2008) has opposite effects on the expression of these subtypes in the striatum. These findings may possibly explain the recent evidence of a dominance of purely ␣6*-sensitive responses in the nAc, whereas ␣4 responses dominate in the CPu (Exley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent experiment has added further complexity. It was found that the decrease in overall conotoxinMII binding observed after oral nicotine administration is due to two opposite effects on different α6* subtypes: a decrease in the α4α6β2* subtype and an increase in the α6(nonα4)β2* subtype [118].…”
Section: Regulation Of Native Subtypes By Chronic Nicotine Exposurementioning
confidence: 99%
“…Accordingly, α4-/-mice chronically treated with oral nicotine show increased αconotoxinMII binding in striatum [118].…”
Section: Regulation Of Native Subtypes By Chronic Nicotine Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The lack of cotinine-induced up-regulation of ␣6␤2␤3 is potentially related to its action on only a portion of this receptor population. This effect could also partially explain discrepancies between groups that detect upregulation (7,55,56) or down-regulation (57) in varying brain regions based on concentrations of nicotine or cotinine present. These studies show that nicotine's primary metabolite, cotinine, has a similar effect on the trafficking and assembly of nAChRs as seen with nicotine.…”
Section: Discussionmentioning
confidence: 97%